IMPLEMENTASI METODE MUROJAAH DAN ZIADAH DALAM MENINGKATKAN KUALITAS MENGHAFAL AL-QUR'AN - Inna Fil Jannati; Suhadi Suhadi; Yetty Faridatul Ulfah (Raudhah - Proud To Be Professional, 2023)
This study aims to determine, 1) the implementation of the murojaah and ziadah methods in improving the quality of students' Al-Qur'an memorization. 2) to find out the inhibiting and supporting factors in memorizing the Al-Qur’an for students at the Tahfidz Amal Syuhada Gajahan House, Surakarta. This study used a qualitative method with a descriptive approach. This research was conducted at the Tahfidz Al-Qur'an Amal Syuhada Gajahan House, Surakarta. The subjects in this study were from the management of the Tahfidz Al-Qur'an Amal Syuhada House, ustadz/ustadzah, and students. Data collection techniques were carried out by interviews, observation, and documentation. Meanwhile the data analysis technique used data reduction techniques, data presentation, and drawing conclusions. The results of the research on the implementation of the murojaah and ziadah methods in memorizing the Qur'an based on interviews, observations, and documentation show that 1) the implementation of using the murojaah and ziadah methods in memorizing the Al-Qur'an can be carried out, but there are few obstacles in the process of carrying out these methods, including that students have not fully mastered tajwid and tahsin, intentions that are slowly starting to fade, impatient in the process of memorizing slowly and carefully from verse to verse,: 2) there are several supporting factors in depositing students' memorization to ustadzah, namely: Learning tahsin and tajwid before memorizing the Qur'an, students use one type of mushaf in memorizing the Qur'an, there are guided murojaah activities (sima'an) from the ustadzah. Keywords : tahfidz, methods, application.